2019
DOI: 10.1108/mmms-05-2018-0103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal radiation and magnetohydrodynamics on Ree-Eyring fluid flows through porous medium with slip boundary conditions

Abstract: Purpose The purpose of this paper is to investigate the three fundamental flows (namely, both the plates moving in opposite directions, the lower plate is moving and other is at rest, and both the plates moving in the direction of flow) of the Ree-Eyring fluid between infinitely parallel plates with the effects of magnetic field, porous medium, heat transfer, radiation and slip boundary conditions. Moreover, the intention of the study is to examine the effect of different physical parameters on the fluid flow.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…18 The impact of 3 on the concentration (y) Fig. 19 The impact of Br on the temperature (y) Fig. 20 The impact of on the temperature (y) Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The impact of 3 on the concentration (y) Fig. 19 The impact of Br on the temperature (y) Fig. 20 The impact of on the temperature (y) Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Numerical solutions for unsteady flows of a MHD Jeffrey fluid between parallel plates through a porous medium were discovered by Ramesh and Joshi [18]. Effects of thermal radiation and magnetohydrodynamics on Ree-Eyring fluids flows through porous medium with slip boundary conditions were developed by Ramesh and Eytoo [19]. Venkata Satya Narayana et al [20] studied numerical study of a Jeffrey fluid over a porous stretching sheet with heat source/sink.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that thermal boundary layer enhances for increasing values of Biot number. Ree-Eyring uid over a parallel plate has been studied by Ramesh and Eytoo [27] considering heat transfer and slip boundary conditions. They analysed the e ect of porous medium and Ree-Eyring uid parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The expressions for the distributions of temperature, concentration and velocity were computed and skin friction, Nusselt number and Sherwood number were analyzed. Ramesh and Eytoo [11] examined the effect of diverse physical parameters on fluid flow. Three Ree-Eyring fluid between infinitely parallel plates with the effects on various parameters were considered.…”
Section: Introductionmentioning
confidence: 99%